Application of Open Street Maps Technology for Android-Based Blood Donation Applications - Zulkifli, Ahmad (Journal of ICT Applications System, 2023)
Blood donation is a person's voluntary giving of blood for the purpose and purpose of blood transfusion for other people in need. These activities must be carried out by parties who are authorized and competent in their fields so that they can run and bring the expected benefits. PMI Kampar Regency through the Blood Donation Unit (UDD) in carrying out blood donation activities still uses traditional systems so it is less effective and efficient. Many people find it difficult to get information about blood donation schedules, donor data and also the latest blood stock. Based on these problems, a Blood Donation Application with Android-based Open Street Maps technology is needed. This research uses the Waterfall method by analyzing needs, designing the system, installing, testing and ending with operation. In collecting data, the author also conducted field observations, interviews and literature studies from various supporting books and previous research. This application was built based on Android using the Java programming language and MySQL database as data storage. This application must use GPS (Global Positioning System) to track the coordinates of the user's location